1989
DOI: 10.1254/jjp.50.271
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of eperisone on isolated dog saphenous arteries and veins.

Abstract: Abstract-Effects of eperisone, an antispasmodic in skeletal muscle, were inves tigated in helical strips of dog saphenous artery and vein. Eperisone relaxed saphenous arteries and veins previously contracted with norepinephrine, serotonin, acetylcholine, K+, or Bat+; but in contrast, it produced contractions in the blood vessels contracted with prostaglandin (PG) Fla. Treatment with eperisone at tenuated the contractions induced by norepinephrine and serotonin in the arteries and those by clonidine and phenyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…They act centrally by relaxing skeletal and vascular smooth muscles to improve circulation and suppress pain reflex 3,4. These drugs are usually prescribed in combination with NSAIDs as painkillers.…”
Section: Discussionmentioning
confidence: 99%
“…They act centrally by relaxing skeletal and vascular smooth muscles to improve circulation and suppress pain reflex 3,4. These drugs are usually prescribed in combination with NSAIDs as painkillers.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that eperisone blocks muscarinic receptors at the effector site. This antimuscarinic effect of eperisone has been re cently reported in isolated dog saphenous arteries and veins (14). Some antispasmodics such as trihexyphenidyl and benztropine exert their antispasmodic effect, at least in part, through blockade of muscarinic receptors (15).…”
Section: Discussionmentioning
confidence: 73%
“…32 Moreover, treatment with eperisone attenuates the contractions induced by norepinephrine and serotonin in the arteries, as well as the contractions induced by clonidine and phenylephrine in the veins. 32 In healthy volunteers, a single dose of eperisone 300 mg has a sympatho-suppressive action and enhances the blood flow in resting skeletal muscles, with no effect on the sympathetic nerve activity in actively contracting muscles, eg, while standing or hand-gripping. 18 Thus, in patients with LBP, eperisone is also expected to improve the blood flow to muscles and improve the hypoxic condition.…”
Section: Discussionmentioning
confidence: 99%
“…31 With reference to this, preclinical studies have shown that ep- erisone exerts several activities on the saphenous artery and veins, thus regulating the blood flow to skeletal muscles of the lower limbs. 32,33 For example, eperisone relaxes the saphenous arteries and veins previously contracted by norepinephrine, serotonin, acetylcholine, potassium, or barium. 32 Moreover, treatment with eperisone attenuates the contractions induced by norepinephrine and serotonin in the arteries, as well as the contractions induced by clonidine and phenylephrine in the veins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation